STUDIES OF DEPRAVED APPETITE IN EGYPTIAN CATTLE - Mohamed M., Mohamed Saied (International Journal of Research -GRANTHAALAYAH, 2018)
The study was carried out on forty-nine (49) cattle cases were clinically healthy animals with average body condition. They were clinically, and laboratory examined proved as healthy cattle and they are free from internal and external parasites were kept as controls while other one hundred (100) cattle animals were suffering from depraved appetites. All animals were belonged to the villages scattered in the Qena Governorate Egypt. Blood samples were taken from the external jugular vein, and then centrifuged and stored until analyses. Blood was taken aseptically from all the animals and transported to laboratory for biochemical analysis for estimation of macro and micro elements in diseased animals. Fecal samples was taken aseptically from all the animals and transported to laboratory for the presence of internal parasites. The results showed a highly significant effect of copper, iron, chloride, and sodium significant at (P<0.01), and low significant of protein, zinc, phosphorus and calcium at (P<0. 05). The aim of this work was to follow the changes, during the early diagnosis of depraved appetite on some trace elements, protein and internal parasites.